Producing of chocolate milk containing microencapsulated probiotic bacteria as a functional food for use in time of war - R ghasemnezhad; V Razavilar; K Khosravi Darani (فصلنامه ابن سینا)
Background: Probiotic milk products with valuable nutritional and health properties is one the most important issues of nutrition and medicine. The aim of present study was to produce chocolate milk containing microencapsulated probiotic bacteria.